Impact of personal protective equipment on the clarity of vision among trachoma survey graders and trichiasis surgeons in the context of COVID-19 - Michaela Kelly; Stephanie Palmer; Emma M Harding-Esch; Paul Courtright; Harran Mkocha; Donal Bisanzio; Nicholas Olobio; Jeremiah M Ngondi; Ehtisham Ul Hassan; Sue-Chen Apadinuwe; Michael Dejene; Philip Downs; et al. (BMJ Open Ophthalmology, 2023)
Background/aims The COVID-19 pandemic necessitated the use of personal protective equipment for those involved in trachoma survey grading and trichiasis surgery. We sought to determine which configuration of a face shield would be less likely to impact grading accuracy and ability to conduct trichiasis surgery. The research also included assessment of comfort, ease of cleaning and robustness.Methods There were three research phases. In phase 1, assessment of four potential face shield configurations was undertaken with principal trachoma graders and trichiasis surgeon trainers to decide which two options should undergo further testing. In phase 2, clarity of vision and comfort (in a classroom environment) of the two configurations were assessed compared with no face shield (control), while grading trachomatous inflammation—follicular (TF). The second phase also included the assessment of impact of the configurations while performing trichiasis surgery using a training model. In phase 3, face shield ease of use was evaluated during routine surgical programmes.Results In phase 2, 124 trachoma graders and 28 trichiasis surgeons evaluated the 2 face shield configurations selected in phase 1. TF agreement was high (kappa=0.83 and 0.82) for both configurations compared with not wearing a face shield. Comfort was reported as good by 51% and 32% of graders using the two configurations. Trichiasis skill scores were similar for both configurations.Conclusion The face shield configuration that includes a cut-out for mounting the 2.5× magnifying loupes does not appear to impact the ability or comfort of trachoma graders or trichiasis surgeons to carry out their work.